Gender Effects on Central Highlands Community-based Tourism Demand - Duong Ngoc Lang; Pham Hong Long, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
The paper uses VOSviewer to examine research on tourist demand and gender in tourism development to gain an overview of the research environment and associated research materials worldwide, as well as in the Central Highlands of Vietnam in particular. Based on a previously examined model of community-based tourist demand in the Central Highlands, this study employs AMOS multigroup analysis to establish the impact of gender on the link between independent and dependent factors. The research findings establish how gender impacts each particular need, with men and women having varying degrees of influence. The study suggests several consequences based on the research findings that can be implemented in the Central Highlands to better fulfill and serve the requirements of local visitors for community-based tourism, thereby creating the groundwork for future growth.Received 13th March 2023; Revised 5th April 2023; Accepted 15th April 2023